ROLE OF REGIONAL PARTIES IN 17TH LOK SABHA ELECTIONS: A THEORETICAL STUDY - Bambole, Rajnish G. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The 17th Lok Sabha elections in India in 2019 were a dynamic shift in Indian politics where regional parties were important, sometimes even decisive. Instead of national parties like the BJP and the Congress opposing the existence of two separate formations, there is a sense of emergence of external leadership among some national parties, such as the process of the leader of the government becoming publicly detached from the party. This paper analyses their importance regionally in the 2019 electoral exercise through their strategies adopted while forming alliances and performances in specific states. Such findings provide a deeper insight into how regional parties focus their agenda on local issues and regional identities, thereby shaping the national political debate-outcomes. Thus, through a precise analysis of success and failure by regional parties, it intends to highlight their growing importance in contemporary politics with respect to the overall balance of power in relation to the Lok Sabha. According to the findings, while regional parties continue to play local politics, this possibly ensures significant space for alliances as they then become the ideal key to certain policy decisions and, indeed, national governance.